The rise of proftability in sheep production by out of season induction of heat in ewes - Mekić, Cvijan; Trifunović, Grigorije; Novaković, Zorica; Vujić, Radosav; Romić, Dragan (Economics of Agriculture, 2010)
The paper presents the results for the sexual activity in ewes stimulated by progestagene substance fluorogestonacetate (FGA) in anoestral period. Synchronization was performed in late August and early May of 2009. The treatment was conducted in the ewes in the type of Sjenička improved sheep and total of 100 adult heads was treated. After 12 days, when the sponge was extracted from the ewes they received 1000 i j PMSG intramuscularly. The frst mating was performed 48 hours after inserting PMSG, and the second one 72 hours after »service by hand» It was asserted that the estrus was manifested in 98. 00% ewes in the number of treated ones. An average fertility in ewes was 183. 00% Number of lambs per treated ewe was 1,.83 and 1. 93 lambs were obtained per lambed breeding female. Number of sterile ewes was 3. 00%. The trial showed that satisfying results have been obtained by using the sponge soaked in fluorogestonacetate (FGA) + PMSG in the conditions of natural mating with synchronization out of season in adult ewes in Sjenička improved type. The 63 lambs more were obtained in relation to regular seasonal mating and wider area of growing of mentioned genotype was asserted as well.